Analyzing and Strategizing the Development of Entrepreneurial Activity Based on the Principles of Increasing Productivity (Illustrated by the Example of Developed Countries and Ukraine) - Borys Volodymyrovych Burkynskyi; Valeriy Fedorovych Goryachuk; Oleksandr Ivanovych Laiko; Volodymyr Mytrofanovych Lisyuk; Nataliia Leonidivna Shlafman; Olena Volodymyrivna Bondarenko (Comparative Economic Research. Central and Eastern Europe, 2021)
The article presents the results of a comparative analysis of productivity in developed countries, including EU countries and Ukraine. Hypotheses about the identity of the deindustrialization factor as the main cause for productivity decrease for both the Ukrainian economy and the economic systems of developed countries are verified. Purpose of the article: To develop a comprehensive methodological approach to strategizing and state regulation of the business environment based on guidelines developed according to the results of a comparative analysis of the productivity of entrepreneurial activities and focused on maximizing the creation of added value, which is a criterion for increasing the productivity of entrepreneurial activities. Methods used: A review of the scientific literature, a comparative analysis of the productivity of entrepreneurial activity in developed countries and Ukraine, including time series analysis, calculating growth rates of per capita value-added, and factor analysis of key obstacles that hinder the growth of the productivity of innovative entrepreneurial activity. The contribution made to the theory and methodology of productivity includes the proposed definition of the economic category "productivity of entrepreneurial activity"; general methodological principles of forming a strategy for improving the productivity of entrepreneurial activities are established; taking into account the best international experience, the main principles of state regulation of the entrepreneurial environment are laid down; it is established that the purpose of the strategy for improving the productivity of entrepreneurial activity is to provide the state with favorable business conditions, i.e., to create a favorable entrepreneurial environment and make it possible to identify and use hidden assets of entrepreneurial structures to develop value-added chains, the growth of which is a criterion for increasing productivity.
Keywords: O38; O47; O57; 330; productivity of entrepreneurial activity; deindustrialization; strategy; value-added maximization